The strategic management in the conditions of innovative economy formation - Magay Т. P. (Journal of Economic Research & Business Administration, 2015)
The article describes approaches to strategic management of companies’ development. Realization of strategic management is connected with problems in which basis indicators of dynamism, variability of the external and internal environment and a tendency of innovative development of the economy which decision makes scientific and practical value are put. The basic elements, and tendencies are outlines and the model of strategic management of companies’ development in the emerging innovation economy of Kazakhstan is formed. The structure of cluster formation that has practical importance in the manufacturing industry is offered. Cluster strategy is directed on creating separate groups of enterprises geographically close and connected among themselves. They will be able to play a role of “growth points” national economy. By potential clusters of economy of Kazakhstan we can determine the following: tourism cluster, mechanical engineering cluster, in particular oil and gas mechanical engineering, cluster of the textile industry, food industry and others.